EFFECTIVENESS OF ORGANIZATIONAL WORK IN PUBLIC ADMINISTRATION - Nitta C. Sasmita; Charisma A. Fitrananda (Universitas Pasundan, 2020)
Organizations that are private in carrying out activities, the emphasis lies in getting a profit or profit, therefore proper organizational activities and can achieve optimal goals can be realized, so that waste is avoided and all the potential that is owned will be more beneficial for the achievement of common interests. This includes higher education organizations. Administrativeactivities are generallyassociatedwithplanning, organizing, controlling, placing, directing, motivating, communicating and making decision activities carried out bye achorganization with the aimofcoordinating various resources owned by the company, so that a productor service will be produce defficient. In such circumstances, in carrying out their duties, without exception all member sof the organization need to work to gether in order to lead to the achievement of the main goals of the organization. All these different activities can be harmonized with one another and gohand in hand to ward the ultimate attainment which is directing and harmonizing. Organizational effective nessis the result of work that is right on target and effective in accordance with predetermined planning or in accordance with the desired results at various levels of the organization in order to achieve mutually determined targets. This research states that the main influencef actors on organizational effectiveness are Organizational Characteristics, Environmental Characteristics, Characteristics of Workers and Management policies and practices. The formation of work units in anorganization is an attempt to achieve goals. The work unit must always have a main task and function as a basis for determining plans.